2018
DOI: 10.1186/s13063-018-2803-4
|View full text |Cite
|
Sign up to set email alerts
|

Patient understanding and acceptability of an early lung cancer diagnosis trial: a qualitative study

Abstract: BackgroundThe ELCID (Early Lung Cancer Investigation and Diagnosis) trial was a feasibility randomised controlled trial examining the effect on lung cancer diagnosis of lowering the threshold for referral for urgent chest x-ray for smokers and recent ex-smokers, aged over 60 years with new chest symptoms. The qualitative component aimed to explore the feasibility of individually randomising patients to an urgent chest x-ray or not and to investigate any barriers to patient recruitment and participation. We int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 34 publications
(47 reference statements)
0
14
0
1
Order By: Relevance
“…[2018], reassurance of not having LC is a key motivational factor to participate in LCS (44). This was also seen in the study of Byrne et al…”
Section: Early-detection Benefitsmentioning
confidence: 64%
See 1 more Smart Citation
“…[2018], reassurance of not having LC is a key motivational factor to participate in LCS (44). This was also seen in the study of Byrne et al…”
Section: Early-detection Benefitsmentioning
confidence: 64%
“…Their role is so important because the lack of understanding of the information in the patient's perspective could result in no participation. Moreover, many participants relay on their health professional to make the decision for them on whether to undergo screening or not (44).…”
Section: Trust In Referring Cliniciansmentioning
confidence: 99%
“…96 Qualitative research has consistently identified stigma as a barrier to lung cancer screening uptake in the UK and the US. 38,57,93,97 In addition to acting as a direct barrier to screening uptake, stigma may contribute to misreporting of smoking status to health professionals, commonly seen in smoking cessation clinical trials. 98 This may indirectly contribute to low screening uptake via the very poor accuracy of smoking status recorded in electronic health records, as discussed below, leading to non-identification of high-risk participants.…”
Section: Stigmamentioning
confidence: 99%
“…Qualitative research has consistently identified stigma as a barrier to lung cancer screening uptake in the UK and the US 38,57,93,97 . In addition to acting as a direct barrier to screening uptake, stigma may contribute to misreporting of smoking status to health professionals, commonly seen in smoking cessation clinical trials 98 .…”
Section: Stigmamentioning
confidence: 99%
“…The integrated qualitative study was carried out with the aim of exploring the feasibility of individually randomising patients to an urgent chest X-ray or not and to investigate any barriers to patient recruitment and participation. A previous paper reported on patient experiences of participating in the trial [ 14 ]. This current paper reports on practice staffs’ experiences of participating in the trial.…”
Section: Introductionmentioning
confidence: 99%